Body mass index, inflammatory biomarkers and neurocognitive impairment in HIV-infected persons. Issue 3 (16th March 2017) - Okafor, Chukwuemeka N.; Kelso, Natalie E.; Bryant, Vaughn; Burrell, Larry E.; Míguez, Maria Jose; Gongvatana, Assawin; Tashima, Karen T.; de la Monte, Suzanne; Cook, Robert L.; Cohen, Ronald A.
Abstract: To determine the relationships among body mass index (BMI), and HIV-associated neurocognitive impairment and the potential mediating effects of inflammatory cytokines. Among the HIV-infected individuals ( N = 90) included in this study, obesity was associated with slower processing speed ( β = −.229, standard error (SE) = 2.15, p = .033), compared to participants with a normal BMI, after controlling for psychosocial and HIV clinical factors. Serum concentrations of the interleukin-16 (IL-16) cytokine were significantly associated with slowed processing speed ( β = −.235, SE = 1.62, p = .033) but did not mediate the relationship between obesity and processing speed These findings suggest that obesity may contribute to cognitive processing speed deficits in HIV-infected adults. Elevated concentrations of IL-16 are also associated with slowing, though the results suggest that obesity and IL-16 may exert independent effects.